Lessons Learned from the Creation of a Center of Excellence in Low Vision and Vision Rehabilitation in Wenzhou, China. (September 2017) - Marinoff, Rebecca; Heiberger, Michael H.
A model Center of Excellence in Low Vision and Vision Rehabilitation was created in a health care setting in China utilizing an inter-institutional relationship with a United States optometric institution. Accomplishments of, limitations to, and stimuli to the provision of low vision and vision rehabilitation services are shared.